Rhythmic gymnastics: profile of scientific production in journals in Latin America, the Caribbean and Iberian countries - Moraes, Leticia Cristina Lima (2019)
This paper aims at mapping knowledge production of rhythmic gymnastics published in Latin American, Caribbean and Iberian journals. To this end, a descriptive exploratory proposal was chosen, listing articles indexed in the following databases: Scielo, Lilacs, and Medline, which were accessed through the interface of the Virtual Health Library and Redalyc. As a result, 48 articles were found in 27 different journals between 2001 and 2017. The most researched topic was training, corresponding to 41.67%. Despite the predominance of this axis, there was a notorious epistemological plurality including: health, psychological, educational, social, cultural, and historical aspects. Therefore, the existence of an auspicious scenario is concluded for an area that is looking for scientific consolidation.  Further studies are needed based on other ways of approaching this sport, both quantitatively and qualitatively.